Kesulitan Guru Dalam Pemanfaatan Fitur Komunitas Belajar Pada Platform Merdeka Mengajar (PMM) Di SDN 182/1 Hutan lindung - Agnes Pebrika; Ahmad Hariandi; Suci Hayati (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
This study aims to describe the utilization of the learning community feature on the Merdeka Mengajar Platform (PMM) and identify the challenges faced by teachers in accessing and using this feature at SDN 182/1 Hutan Lindung. The research was conducted at SDN 182/1 Hutan Lindung during the odd semester of the 2024/2025 academic year. A qualitative method with a case study approach was employed. Data were collected through interviews, observations, and documentation involving teachers of grades IV, V, and VI. The validity of the data was tested using triangulation of techniques, sources, and time. The findings indicate that the use of the learning community feature on PMM is still low. Teachers only utilized this feature at the initial stages, such as joining a community or participating in one specific activity, but there was no continuity in its use. Activities within the learning community were limited because teachers more frequently used other features, such as self-training and teaching tools, which were considered more relevant to supporting their daily tasks. Additionally, the lack of routine habits in accessing this feature also contributed to its limited use. The challenges faced by teachers in accessing and utilizing the learning community feature include several aspects. Limited technological skills caused difficulties in navigating the PMM interface. High workloads made it challenging for teachers to allocate time to explore features like the learning community. Low teacher motivation to actively participate was influenced by the lack of support from the school environment and limited supporting facilities.